A quantitative modeling of the contributions of localized surface plasmon resonance and interband transitions to absorbance of gold nanoparticles - Zhu, S. (2013)
A quantitative modeling of the contributions of localized surface plasmon resonance (LSPR) and interband transitions to absorbance of gold nanoparticles has been achieved based on Lorentz–Drude dispersion function and Maxwell-Garnett effective medium approximation. The contributions are well modeled with three Lorentz oscillators. Influence of the structural properties of the gold nanoparticles on the LSPR and interband transitions has been examined. In addition, the dielectric function of the gold nanoparticles has been extracted from the modeling to absorbance, and it is found to be consistent with the result yielded from the spectroscopic ellipsometric analysis.